2014
DOI: 10.1371/journal.pone.0109549
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Goiter and Thyroid Nodules before and after Implementation of the Universal Salt Iodization Program in Mainland China from 1985 to 2014: A Systematic Review and Meta-Analysis

Abstract: ObjectivesWe comprehensively estimated the prevalence of goiter and thyroid nodules (TNs) before and after the implementation of the Universal Salt Iodization (USI) program in mainland China and provided information for creating effective health policies.MethodsPubMed, Google Scholar, CNKI, Chinese Wanfang and Chongqing VIP databases were searched for relevant studies from Jan 1985 to Feb 2014. Data from eligible citations were extracted by two independent reviewers. All analyses were performed with Stata 11.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 35 publications
5
52
3
1
Order By: Relevance
“…However, to our knowledge, other studies did not find associations of dietary iodine intake from edible seaweed or supplements with thyroid cancer incidence (Kolonel et al, 1990;Horn-Ross et al, 2001;Zhang et al, 2013). Although ecological studies observed increased thyroid cancer incidence in Denmark (Blomberg et al, 2012) and China (Zhao et al, 2014) after the implementation of compulsory iodine supplementation, such studies could be susceptible to detection bias related to thyroid cancer screening of asymptomatic individuals and improvement in diagnostic modalities (Ahn et al, 2014;La Vecchia et al, 2015). In sum, it is inconclusive whether excessive iodine intake is harmful or not, although the present study did not suggest such an effect.…”
Section: Discussioncontrasting
confidence: 54%
“…However, to our knowledge, other studies did not find associations of dietary iodine intake from edible seaweed or supplements with thyroid cancer incidence (Kolonel et al, 1990;Horn-Ross et al, 2001;Zhang et al, 2013). Although ecological studies observed increased thyroid cancer incidence in Denmark (Blomberg et al, 2012) and China (Zhao et al, 2014) after the implementation of compulsory iodine supplementation, such studies could be susceptible to detection bias related to thyroid cancer screening of asymptomatic individuals and improvement in diagnostic modalities (Ahn et al, 2014;La Vecchia et al, 2015). In sum, it is inconclusive whether excessive iodine intake is harmful or not, although the present study did not suggest such an effect.…”
Section: Discussioncontrasting
confidence: 54%
“…However, in 2013 it was reported that the MUI of school-age children in Xi'an was 280.5 μg/L [8], higher than the standard levels proposed by World Health Organization (WHO) [9], indicating that the iodine intake of population in Xi'an was more than adequate. Actually, many inland areas of China have experienced the similar conversion from iodine-deficiency to iodine-sufficiency or more than adequacy during the past two decades [10], which necessitates the establishment of accurate RIs. More importantly, although China has three RIs of thyroid hormones so far, the three RIs were all from hospital-or communitybased studies or from studies not excluding patients with abnormal ultrasonography findings [11][12][13].…”
Section: Data and Sample Collectionmentioning
confidence: 99%
“…For example this prevalence is from 8 to 65% in autopsy and from 19 to 35% in ultrasound survey (2). According to retrospective studies, only 4-5% of thyroid nodules are malignant (3)(4)(5). Several risk factors have been reported for the presence of carcinoma in thyroid nodules, and one of them is the size of the thyroid nodules (6).…”
Section: Introductionmentioning
confidence: 99%